2018
DOI: 10.1024/0301-1526/a000727
|View full text |Cite
|
Sign up to set email alerts
|

Atherosclerosis knowledge – diagnosis and management in primary care

Abstract: Our study demonstrates that GPs' knowledge about atherosclerosis disease varies significantly depending on disease location. GPs diagnose correctly but need to be backed up for their management of patients with atherosclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 16 publications
2
10
1
Order By: Relevance
“…This study shows that there are differences in GPRs' awareness and management of atherosclerotic disease depending on its location. The best awareness was for TIA such as in our previous GPs' study [3]. Unlike the study about GPs, here, we don't find any significant difference between SA and IC.…”
Section: Discussioncontrasting
confidence: 70%
See 2 more Smart Citations
“…This study shows that there are differences in GPRs' awareness and management of atherosclerotic disease depending on its location. The best awareness was for TIA such as in our previous GPs' study [3]. Unlike the study about GPs, here, we don't find any significant difference between SA and IC.…”
Section: Discussioncontrasting
confidence: 70%
“…As we found the same trends in the two studies concerning GPs' and GPRs' knowledge of atherosclerosis disease, this questions the quality of initial training in French medical Faculties [3]. TIA was the best-known disease in our studies (19.9% for GPRs and 48.2% for GPs), followed by SA (0.9% for GPRs and 3.0% for GPs) and IC (0.4% for GPRs and GPs).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Libby concluded that 2.8% of the participants are aware of atherosclerosis (Libby et al, 2016). The study by Maria Charasson revealed that 96.5% of the participants are aware of atherosclerosis (Charasson et al, 2018). In the present study 87.3% of the participants agreed that low HDL cholesterol can cause atherosclerosis.…”
Section: Resultssupporting
confidence: 58%
“…In a study with 18500 French general practitioners, intermittent claudication was well known, but knowledge of recommendations for further diagnostic workup and treatment of PAD was poor[7].…”
Section: Introductionmentioning
confidence: 99%